Optimasi Microwave Assisted Extraction (MAE) Pada Pigmen Klorofil Pakcoy (Brassica rapa L) - Hanifa, Jilan; Wiyono , Andi Eko; Purnomo , Bambang Herry (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Pak choi (Brassica rapa L.) is a type of green vegetable from the Brassicaceae family that is rich in chlorophyll pigments. The distinctive green color of pak choi indicates a high chlorophyll content, making it a source of natural antioxidants that are useful in warding off free radicals. The abundant chlorophyll content and its biological benefits open up great opportunities to develop pak choi as a functional food raw material. One effective and efficient extraction method is Microwave-Assisted Extraction (MAE), which utilizes microwaves to accelerate the extraction process while maintaining the quality of bioactive compounds. The Response Surface Methodology (RSM) approach is used as a method for designing experiments and optimization. The variables studied include extraction time with a range of 1 to 3 minutes with a solvent volume having a minimum value limit of 100 mL and a maximum of 200 mL. The purpose of this study was to determine the optimum point, so that the right conditions for pak choi extraction using the MAE method can be determined. The results showed that the recommended optimum formula was extraction with a treatment time of 1.82 minutes and a solvent volume of 154.3 mL with a desirability value of 0.876. The extract obtained had characteristics of a yield of 88.114%, chroma of 12.746, and total chlorophyll of 4.969 mg/L. Verification of the optimum conditions of pak choi extract, the average total chlorophyll produced was 5.349 mg/L, Chroma of 11.297, and a yield of 85.53%. Physicochemical testing showed a ° Hue of 143.802, a Total Dissolved Solids (TPT) value of 1.253° Brix, while the pH value of the pak choi extract was 7.05. Keywords : Extract, Chlorophyll, MAE, Pak choi, RSM